Physicochemical and Microbiological Stability of a New Oral Clonidine Solution for Paediatric Use - Verlhac Camille; Lannoy Damien; Bourdon Florence; Titecat Marie; Frealle Emilie; Nassar Carole; Berneron Christophe; Odou Pascal (De Gruyter, 2018)
As many drugs are unavailable for paediatric use, hospital pharmacies are often required to develop suitable formulations themselves. Clonidine is commonly used in paediatrics (in severe hypertension, in opiate withdrawal syndrome, in tics and Gilles de la Tourette syndrome or in anaesthetic premedication) but no appropriate formulation has been drawn up. The aims of this work were to develop an oral solution of clonidine dedicated to children and to assess its physicochemical and microbiological stability.